CBMT-31. HDAC INHIBITION DIMINISHES THE GROWTH OF ENDOGENOUS IDH MUTANT GLIOMAS. (11th November 2019) - Elahi, Lubayna; Garrett, Matthew; Guo, Lea; Condro, Michael; Kawaguchi, Riki; Mehta, Shwetal; Lai, Albert; Pope, Whitney; Kornblum, Harley
Abstract: Histone deacetylase inhibitors (HDACi's) have emerged as a promising class of drugs for treatment of malignancies such as glioblastoma (GBM). Several studies have demonstrated the anti-tumor property of HDACi's against GBM in both in vitro and in vivo experiments. Nonetheless, in clinical trials, HDACi only marginally increased overall survival of patients with GBM. The mixed results of trials with HDACi's in glioma have prompted us to hypothesize that improved selection of patients by tumor characteristics could enhance the efficacy of therapy. We specifically tested the effects of valproic acid (VPA), a HDACi and an antiepileptic drug against IDH mutant gliomas. We have previously demonstrated that our IDH mutant glioma cell lines have gene expression and methylation patterns highly similar to IDH mutant tumors in situ. Mutant IDH1 alters the epigenetic landscape of gliomas leading to the hypermethylation phenotype and transcriptional repression of genes. This repression of genes may contribute to tumorigenesis and progression of IDH mutant gliomas. We found that VPA inhibits the growth of patient-derived IDH1 mutant glioma lines. In addition, RNA sequencing analysis of vehicle and VPA-treated IDH1 mutant glioma cells showed de-repression of several genes previously shown to be downregulated in IDH1 mutant glioma cell lines. We also treated cells with another HDACi LBH589 and found that both VPA and LBH589 upregulates similar gene sets suggesting that HDAC inhibition promotes de-repression of previously repressed genes. Ongoing studies are aimed at determining the molecular mechanism by which VPA regulates the growth of IDH1 mutant tumors.